Use of Whatsapp Application in Organizational Communications in Class II Bukittinggi Corporate Center - Nofianti, Nike; Roem, Elva Ronaning (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Communication is very important in the continuity and success of an interaction both in everyday life and in organizational life. In the communication process, a communicator conveys a message to the communicant using the media. Media as an expansion of information is increasingly developing until emerging communication technology. Smartphones are concrete manifestations of technological advancements created to make it easier for humans to communicate. The growth of communication technology is also marked by an increase in social media. WhatsApp is one of the social media that is widely used for the purpose of socializing or as a message delivery both individuals and groups. Various facilities offered by WhatsApp, in addition to sharing messages between individuals, WhatsApp is also used for work purposes. With the various facilities and uses offered by WhatsApp, it attracts the interest of Bukittinggi Class II Rehabilitation center employees, so that employees can communicate with each other and deliver messages or information related to the tasks and functions of the agency. Therefore, researchers are interested in conducting a study entitled